African philosophy and its hermeneutical turn. Proactivity of Basil-Juléat Fouda - (:unkn) unknown (My University, 2025)
This article highlights the effectiveness of the hermeneutic approach within the framework of African philosophy in general, and in the work of Basil-Juléat Fouda in particular. Without claiming to provide an exhaustive development of African thought, we demonstrate that the link between hermeneutics and African philosophy, recognized by Paulin Hounrondji, is a theme that has been variously explored by philosophers such as Benoît Okolo Okonda, Henri Odera Oruka, Henri Maurier, Issiaka Prosper Laleye, Jeki Kinyongo, Kä Mana, Niamkey Koffi, Nkombe Oleko, Onaotsho Kawende, Phambu Ngoma Binda, Tshiamalenga Ntumba, etc. This theme is further reinforced in Fouda’s proactive offering of a traditional African philosophy, which is inscribed in the dialectical debate of the local and the global with a firm desire “to situate African philosophy within the general movement of philosophical thought, in order to better show its originality”. Moreover, it will be necessary to realise that the hermeneutic rationality, whose rational procedures are more or less held in contempt in Africa, cannot be considered as a supplementary methodological practice, especially since it is an alternative rationality imposed by reality on thought. This is all the more significant given the recognized role of ‘endogenous knowledge’ in the history of thought and life, due to the effects of the perception of knowledge on the evolution of human consciousness, and consequently, the consciousness of belonging to a community, which is accentuated when one seeks to grasp its philosophical relevance.
Keywords: African Research